Design, synthesis, and in silico evaluation of 1,4 dihydropyridine and 3,4 dihydropyrimidine 2(1H)-ones/thione derivatives - Manisha Ashwin Tayde; Suvarna Abhijeet Katti; Anuja Prabhakar Bhosale (Creative Pharma Assent, 2026)
Background: Pyridine and pyrimidine derivatives occupy a central position in medicinal chemistry owing to their broad pharmacological significance. In particular, 1,4-dihydropyridines and 3,4-dihydropyrimidines are known for their anti-hypertensive and anti-anginal activities, encouraging further exploration of their chemical space. Methodology: This study aimed to design and synthesize a novel series of nineteen derivatives (PS-1 to PS-19) based on 1,4-dihydropyridine and 3,4-dihydropyrimidine-2(1H)-ones/thiones, employing a green synthetic strategy. The pharmacological viability of these compounds was assessed through in silico profiling. A catalyst-free